A kind of foamed silicone rubber absorbing material and preparation method thereof
By adding multi-walled carbon nanotubes, iron powder and other components to the silicone rubber-based absorbing material, and using refining, vulcanization and supercritical fluid foaming technology, foamed silicone rubber absorbing materials with low density and high expansion ratio are prepared, which solves the problem of insufficient absorption performance of existing materials in the wide frequency range, and achieves efficient absorption, lightweight and flexible applications.
Patent Information
- Application Number
- CN202510048418.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-04
AI Technical Summary
The existing silicone rubber-based absorbing materials have insufficient absorbing performance in a wide frequency range, high material density, difficult to control the pore structure, and complex preparation process, which cannot meet the technical needs of modern lightweight, flexible and stealth.
Through the combination of components such as methylvinyl silicone rubber, multi-wall carbon nanotubes, iron powder, gas-phase silica and hydroxy silicone oil, combined with refining, vulcanization and supercritical fluid foaming technology, foamed silicone rubber wave absorbing materials with low density and high expansion ratio are prepared to form a tight three-dimensional conductive network to improve wave absorbing performance.
It realizes efficient wave absorption in a wide frequency range, reduces material density, improves the control of pore structure, simplifies the preparation process, and meets the technical needs of lightweight, flexible and stealth.
Smart Images

Figure SMS_1 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a foamed silicone rubber absorbing material and a preparation method thereof. Background Art
[0002] With the rapid development of electronic equipment and wireless communication technology, electromagnetic interference problems are becoming increasingly serious, and the demand for functional absorbing materials is growing rapidly. Traditional electromagnetic shielding materials are mostly metal-based, and achieve shielding functions by reflecting electromagnetic waves. They have defects such as heavy weight, poor flexibility, and easy to generate secondary electromagnetic pollution. They can no longer meet the modern technical requirements of lightweight, flexible and stealth.
[0003] In contrast, absorbing materials absorb electromagnetic wave energy through mechanisms such as magnetic loss, dielectric loss, and multiple reflections, and convert it into heat or other forms of energy, which can effectively eliminate electromagnetic pollution. Silicone rubber has become an ideal matrix material for flexible absorbing composite materials due to its excellent flexibility, high and low temperature resistance, and processing adaptability. However, silicone rubber itself does not have absorbing properties and needs to be functionally modified by filling it with conductive and magnetic fillers.
[0004] In addition, studies have shown that the porous structure inside the material has a significant effect on the absorption performance. The three-dimensional pore structure not only reduces the material density, but also weakens the reflection of electromagnetic waves on the material surface, allowing more electromagnetic waves to enter the system. At the same time, multiple reflections and absorptions can be formed between the multiple interfaces in the pores, causing the electromagnetic wave energy to be lost to a greater extent, thereby achieving the effect of enhancing the electromagnetic wave absorption performance. Therefore, designing composite absorbing materials with porous structures has become a hot topic in current research.
[0005] Although the existing silicone rubber-based absorbing materials meet the requirements of flexible absorbing to a certain extent, they still have the following shortcomings: Insufficient wave absorption performance: The wave absorption mechanism of a single filler is relatively simple, and it is difficult to simultaneously meet the two conditions of good electromagnetic matching performance and high-intensity loss capacity, and it is difficult to achieve efficient wave absorption in a wide frequency range.
[0006] High material density: Traditional silicone rubber absorbing materials enhance the dielectric loss and absorbing performance of the material by adding conductive fillers above the percolation threshold to form a conductive path, but this often requires a higher filling concentration, which inevitably leads to an increase in the overall mass of the material and increased brittleness, which is not conducive to lightweight and flexible applications.
[0007] The pore structure is difficult to control: Although the traditional chemical foaming method can generate a pore structure, the pore size and distribution are difficult to control accurately, and it is impossible to fully utilize the porous structure to improve the electromagnetic wave absorption performance.
[0008] Complex preparation process: In the strategy of constructing a three-dimensional conductive network / skeleton with multiple interfaces, such as based on organic polymer foam, conductive or electromagnetic nanofillers are evenly distributed on the pores attached to the polymer foam to form a conductive path, which has low preparation efficiency and high cost. Supercritical fluid foaming technology can efficiently prepare uniform porous structures and construct a three-dimensional conductive network based on the bubble volume occupancy effect. It is one of the ideal processes for preparing porous composite absorbing materials. Summary of the invention
[0009] The object of the present invention is to overcome the above technical defects and provide a foamed silicone rubber absorbing material and a preparation method thereof that can achieve efficient wave absorption in a wide frequency range.
[0010] The present invention is achieved through the following technical solutions: A foamed silicone rubber absorbing material comprises the following components in parts by weight: 100 parts of methyl vinyl silicone rubber; 7-13 parts of multi-walled carbon nanotubes; 7-13 parts of iron powder; 7-13 parts of fumed silica; 2-4 parts of hydroxy silicone oil; 1-3 parts of peroxide crosslinking agent; The density of the foamed silicone rubber absorbing material is 0.268-0.818 g / cm 3 , expansion ratio 1.5-4.5 times.
[0011] The multi-walled carbon nanotubes have a diameter range of 5-30 nm and a length range of 0.5-2 microns, preferably a diameter range of 5-10 nm and a length of 0.5-2 microns.
[0012] The average particle size of the iron powder is in the range of 10-50 microns, preferably 10-15 microns.
[0013] The specific surface area of fumed silica ranges from 150 to 400 m 2 / g, preferably 180-220 m 2 / g.
[0014] The molecular weight of the methyl vinyl silicone rubber is in the range of 500,000 to 700,000, wherein the vinyl content is 0.13 to 3.79 mol%, and preferably, the vinyl content is 0.80 to 1.79 mol%.
[0015] The viscosity of the hydroxy silicone oil is in the range of 20-40 cst, and the hydroxyl content is in the range of 7-11 mol%.
[0016] The peroxide crosslinking agent is selected from at least one of di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide.
[0017] The preparation method of the foamed silicone rubber absorbing material of the present invention comprises the following steps: banburying methyl vinyl silicone rubber, multi-walled carbon nanotubes, iron powder, fumed silica and hydroxy silicone oil at 90-110° C.; after cooling to room temperature, adding a peroxide crosslinking agent and banburying at 20-35° C. to obtain a mixture; subjecting the banburying mixture to a first vulcanization at 115-145° C. and a pressure of 9-11 MPa for 10-40 minutes, and controlling the crosslinking degree to 40-60%; injecting the sulfide into a supercritical fluid in a high-pressure reactor, and foaming the mixture under the conditions of controlling the temperature to 60-80° C. and the pressure to 14-16 MPa, wherein the gas in the supercritical fluid is selected from at least one of carbon dioxide and nitrogen; and subjecting the mixture to a secondary vulcanization at 180-210° C. for 2-4 hours, to obtain the foamed silicone rubber absorbing material.
[0018] Among them, the degree of vulcanization (i.e., the degree of crosslinking) is controlled by controlling the reaction temperature and time of the first vulcanization, and the degree of crosslinking reaches 40-60%. The degree of crosslinking is determined by referring to the correlation between the storage modulus and the degree of curing of the material after vulcanization. The specific test method is: use dynamic mechanical analysis to test the storage modulus G' of the rubber, the storage modulus when not vulcanized is G'(0), the storage modulus when fully vulcanized is G'(∞), the storage modulus when the vulcanization time is t is G'(t), and the degree of crosslinking when the vulcanization time is t is estimated by the following formula.
[0019]
[0020] The foaming density is controlled by adjusting the ratio of carbon dioxide to nitrogen in the supercritical fluid. The volume ratio of carbon dioxide to nitrogen is in the range of (15-0): (0-15).
[0021] The present invention has the following beneficial effects The present invention provides a crosslinking group through the vinyl group of the methyl vinyl silicone rubber, which can be crosslinked and cured with a peroxide crosslinking agent. Multi-walled carbon nanotubes and iron powder constitute a composite wave absorbing material, and fumed silica is used as a pore proppant. The pre-crosslinking degree is first controlled, and then bubbles are introduced into the matrix through supercritical fluid foaming technology. Through supercritical foaming, a density of 0.268-0.818 g / cm can be obtained. 3 , a foaming material with an expansion ratio of 1.5-4.5 times, and finally a secondary vulcanization is performed to obtain the inventive silicone rubber absorbing material of the present invention. At this time, the same amount of conductive filler can form a more compact three-dimensional conductive network in the composite material under the influence of the volume occupation effect of the bubbles, thereby achieving the purpose of improving the composite material to achieve efficient absorption in a wide frequency range. DETAILED DESCRIPTION
[0022] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0023] The sources of raw materials used in the present invention are as follows: Methyl vinyl silicone rubber A: Vinyl content is 0.80-1.79 mol%, brand number is 110-6, manufacturer is DJ Silicone.
[0024] Methyl vinyl silicone rubber B: Vinyl content is 0.25-0.49 mol%, brand number is 110-4, manufacturer is DJ Silicone.
[0025] Methyl vinyl silicone rubber C: Vinyl content is 0.50-0.79 mol%, brand number is 110-5, manufacturer is DJ Silicone.
[0026] Methyl vinyl silicone rubber D: Vinyl content is 1.80-3.79 mol%, brand number is 110-7, manufacturer is DJ Silicone.
[0027] Multi-walled carbon nanotube A: diameter 5-10 nm, length 0.5-2 microns, manufacturer is Shanghai McLean Biochemical Technology Co., Ltd.
[0028] Multi-walled carbon nanotube B: diameter 20-30nm, length 0.5-2 microns, manufacturer is Shanghai McLean Biochemical Technology Co., Ltd.
[0029] Multi-walled carbon nanotube C: diameter 10-20nm, length 0.5-2 microns, manufacturer is Shanghai McLean Biochemical Technology Co., Ltd.
[0030] Iron powder A: particle size is 10-15 microns, the manufacturer is Qishan Anti-corrosion Protection New Material Technology Research Institute.
[0031] Iron powder B: particle size is 30-40 microns, the manufacturer is Shanghai Jizhi Biochemical Technology Co., Ltd.
[0032] Fumed silica A: Specific surface area 200m 2 / g, the manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd.
[0033] Fumed silica B: Specific surface area 150m 2 / g, the manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd.
[0034] Fumed silica C: Specific surface area 400m2 / g, the manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd.
[0035] Hydroxy silicone oil: The viscosity is 30cst, the hydroxyl content is 9mol%, and the manufacturer is Shenzhen Jipeng Silicone Fluoride Materials Co., Ltd.
[0036] Di-tert-butylperoxyisopropylbenzene: The purity is 96%, and the manufacturer is Shanghai McLean Biochemical Technology Co., Ltd.
[0037] Methyl silicone oil: The viscosity is 30cst, and the manufacturer is Shenzhen Jipeng Silicone Fluoride Materials Co., Ltd.
[0038] Vinyl silicone oil: The viscosity is 30cst, the vinyl content is 1.3%, and the manufacturer is Shenzhen Jipeng Silicone Fluoride Materials Co., Ltd.
[0039] Embodiment and comparative example The preparation method of the foamed silicone rubber absorbing material is as follows: methyl vinyl silicone rubber, multi-walled carbon nanotubes, iron powder, fumed silica, and hydroxy silicone oil (or other silicone oil) are kneaded at 100°C; after cooling to room temperature, a peroxide crosslinking agent is added and kneaded at 20-35°C to obtain a mixture; the kneaded mixture is first vulcanized at a pressure of 10 MPa (specific reaction temperature and time are shown in the table); the sulfide is then injected into a supercritical fluid in a high-pressure reactor, and foaming is performed under the conditions of a temperature of 70°C and a pressure of 15 MPa. The supercritical fluid is shown in the carbon dioxide / nitrogen volume ratio table to control the expansion ratio and material density; and then secondary vulcanization is performed at 200°C for 3 hours to obtain a foamed silicone rubber absorbing material.
[0040] Various test methods: (1) Absorption performance: A vector network analyzer (Keysight N5227B) was used to test the absorption performance of composite foams of different thicknesses in the 8-12 GHz band.
[0041] (2) Compression strength: A universal testing machine (Instron 34TM-30) was used to test the compression properties of the composite foam at room temperature. The compression rate was 1 mm / min. The stress at a compression strain of 50% was used to evaluate the compression strength of the sample. The present invention requires a compression strength of ≥ 0.10 MPa.
[0042] Table 1: Content of each component and test results of the foamed silicone rubber absorbing material of Examples 1-7 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Methyl vinyl silicone rubber A A A B C D A Methyl vinyl silicone rubber content 100 100 100 100 100 100 100 Multi-walled carbon nanotubes A A A A A A B Multi-walled carbon nanotube content 7 10 13 10 10 10 10 Iron powder A 13 10 7 10 10 10 10 Fumed Silica A 7 10 13 10 10 10 10 Hydroxy silicone oil 2 3 4 3 3 3 3 Di-tert-butylperoxyisopropylbenzene 1 2 3 2 2 2 2 First vulcanization temperature ℃ 120 135 150 150 135 125 135 First vulcanization time min 40 20 10 20 30 20 20 Crosslinking degree of the first vulcanization % 40.1 50.6 58.7 48.6 51.2 55.5 52.2 Carbon dioxide / nitrogen volume ratio 10:1 9:6 1:10 9:6 9:6 9:6 9:6 Expansion ratio, times 4.19 2.78 2.26 2.70 2.76 2.47 2.92 <![CDATA[Density, g / cm 3 > 0.27 0.41 0.50 0.46 0.43 0.50 0.39 Minimum reflection loss db / 2.5mm -26.1 -31.5 -26.3 -28.2 -29.1 -28.3 -27.1 Minimum reflection loss db / 2.9mm -26.3 -30.4 -26.5 -27.1 -28.3 -28.0 -27.5 Minimum reflection loss db / 3.3mm -25.7 -31.3 -27.2 -28.0 -28.8 -27.9 -26.8 Compression strengthMpa 0.10 0.18 0.19 0.14 0.16 0.25 0.14 It can be seen from Examples 2 / 4 / 5 / 6 that under the process conditions of the present invention, Example 2 of the methyl vinyl silicone rubber with the preferred vinyl content is easier to control the pre-crosslinking degree, thereby obtaining a better pore structure and improving the wave absorbing effect. It can be seen from Example 4 that the first vulcanization crosslinking is not only related to the vulcanization temperature / time, but also closely related to the vinyl content of the vinyl silicone rubber. When the vinyl content of the vinyl silicone rubber B is low or high, the pre-crosslinking and foaming are more difficult to control than the preferred solution, resulting in a slight decrease in the wave absorbing performance.
[0043] Table 2: Content of each component and test results of the foamed silicone rubber absorbing material of Examples 8-11 Example 8 Example 9 Example 10 Embodiment 11 Methyl vinyl silicone rubber A 100 100 100 100 Multi-walled carbon nanotubes C A A A Multi-walled carbon nanotube content 10 10 10 10 Iron powder A 10 10 10 Iron fan B 10 Fumed Silica A 10 10 Fumed Silica B 10 Fumed Silica C 10 Hydroxy silicone oil 3 3 3 3 Di-tert-butylperoxyisopropylbenzene 2 2 2 2 First vulcanization temperature ℃ 135 135 135 135 First vulcanization time min 20 20 20 20 Degree of crosslinking in the first vulcanization 49.3 51.3 51.9 52.5 Carbon dioxide / nitrogen volume ratio 9:6 9:6 9:6 9:6 Expansion ratio, times 3.16 2.92 2.85 2.92 <![CDATA[Density, g / cm 3 > 0.36 0.39 0.40 0.39 Minimum reflection loss db / 2.5mm -28.5 -27.1 -30.4 -30.5 Minimum reflection loss db / 2.9mm -27.3 -27.1 -28.8 -29.2 Minimum reflection loss db / 3.3mm -27.8 -26.9 -30.7 -30.8 Compression strength 0.13 0.15 0.17 0.16 It can be seen from Examples 2 / 7 / 8 that the multi-walled carbon nanotubes of Example 2 with the preferred parameters have a better wave absorbing effect.
[0044] It can be seen from Example 2 / 9 that the wave absorption effect of Example 2 with the iron powder of the preferred particle size is better.
[0045] It can be seen from Examples 2 / 10 / 11 that Example 2 of the fumed silica with the preferred specific surface area has better wave absorption effect and higher compression strength.
[0046] Table 3: Content of each component and test results of foamed silicone rubber absorbing materials in comparative examples 1-7 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Methyl vinyl silicone rubber A 100 100 100 100 100 100 100 Multi-walled carbon nanotubes A 10 10 20 15 5 10 10 Iron powder A 10 10 0 5 15 10 10 Fumed Silica A 10 10 10 10 10 0 10 Hydroxy silicone oil 3 3 3 3 0 Methyl silicone oil 3 Vinyl silicone oil 3 Di-tert-butylperoxyisopropylbenzene 2 2 2 2 2 2 2 First vulcanization temperature ℃ 135 135 135 135 135 135 135 First vulcanization time min 20 20 20 20 20 20 20 Degree of crosslinking in the first vulcanization 49.8 53.0 51.3 48.6 51.1 50.8 52.7 Carbon dioxide / nitrogen volume ratio 9:6 9:6 9:6 9:6 9:6 9:6 9:6 Expansion ratio, times 2.56 1.53 2.79 2.65 2.60 1.47 2.26 <![CDATA[Density, g / cm 3 > 0.44 0.74 0.39 0.41 0.50 0.73 0.50 Minimum reflection loss db / 2.5mm -25.6 -24.6 -19.2 -21.2 -23.1 -25.5 -24.7 Minimum reflection loss db / 2.9mm -26.3 -23.4 -18.1 -22.2 -25.2 -25.1 -24.2 Minimum reflection loss db / 3.3mm -26.7 -24.2 -19.6 -24.1 -27.2 -25.4 -23.6 Compression strengthMpa 0.07 0.20 0.12 0.13 0.12 0.06 0.07 It can be seen from Comparative Example 1 that the compression strength of Comparative Example 1 using methyl silicone oil is too low and the wave absorbing performance is insufficient.
[0047] It can be seen from Comparative Example 2 that although vinyl silicone oil can improve the degree of crosslinking, it has poor dispersion performance for other raw materials, resulting in poor microwave absorption performance of Comparative Example 2.
[0048] It can be seen from comparative examples 3 / 4 / 5 that when the ratio of multi-walled carbon nanotubes to iron powder is not within the range of the present invention, the wave absorbing effect is poor.
[0049] It can be seen from Comparative Example 6 that the support of the foaming material is insufficient when the fumed silica is not contained, and the wave absorbing performance is reduced due to insufficient uniformity of the pores.
[0050] It can be seen from Comparative Example 7 that when hydroxy silicone oil is not contained, the compatibility of the components is insufficient, resulting in decreased wave absorption performance and compressive strength.
[0051] Table 4: Content of each component and test results of foamed silicone rubber absorbing materials in comparative examples 8-10 Comparative Example 8 Comparative Example 9 Comparative Example 10 Methyl vinyl silicone rubber A 100 100 100 Multi-walled carbon nanotubes A 10 10 10 Iron powder A 10 10 0 Fumed Silica A 10 10 10 Hydroxy silicone oil 3 3 3 Di-tert-butylperoxyisopropylbenzene 2 2 2 First vulcanization temperature ℃ / 130 130 First vulcanization time min / 60 1010 Degree of crosslinking in the first vulcanization / 76.3 36.5 Carbon dioxide / nitrogen volume ratio 9:6 9:6 9:6 Expansion ratio, times 1.01 1.00 1.38 <![CDATA[Density, g / cm 3 > 1.12 1.13 0.82 Minimum reflection loss db / 2.5mm / / -15.2 Minimum reflection loss db / 2.9mm / / -16.3 Minimum reflection loss db / 3.3mm / / -15.3 Compression strengthMpa / / 0.57 It can be seen from Comparative Example 8 that if foaming is carried out directly without vulcanization, foaming will not be possible due to the low melt strength.
[0052] It can be seen from Comparative Example 9 that when the first vulcanization is excessive, foaming cannot be performed due to the high viscosity, and a solid silicone rubber is obtained.
[0053] It can be seen from Comparative Example 10 that when the first vulcanization degree is too low, the melt viscosity is low and the foaming degree is insufficient, which will significantly affect the absorbing performance.
Claims
1. A foamed silicone rubber absorbing material, characterized in that: By weight, it includes the following components: 100 parts of methyl vinyl silicone rubber; 7-13 parts of multi-walled carbon nanotubes; 7-13 parts of iron powder; 7-13 parts of fumed silica; 2-4 parts of hydroxy silicone oil; 1-3 parts of peroxide crosslinking agent; The density of the foamed silicone rubber absorbing material is 0.268-0.818 g / cm 3 , expansion ratio 1.5-4.5 times.
2. The foamed silicone rubber absorbing material according to claim 1, characterized in that: The multi-walled carbon nanotubes have a diameter range of 5-30 nm and a length range of 0.5-2 microns, preferably a diameter range of 5-10 nm and a length of 0.5-2 microns.
3. The foamed silicone rubber absorbing material according to claim 1, characterized in that: The average particle size of the iron powder is in the range of 10-50 microns, preferably 10-15 microns.
4. The foamed silicone rubber absorbing material according to claim 1, characterized in that: The specific surface area of fumed silica ranges from 150 to 400 m 2 / g, preferably 180-220 m 2 / g.
5. The foamed silicone rubber absorbing material according to claim 1, characterized in that: The molecular weight of the methyl vinyl silicone rubber is in the range of 500,000 to 700,000, wherein the vinyl content is 0.13 to 3.79 mol%, and preferably, the vinyl content is 0.80 to 1.79 mol%.
6. The foamed silicone rubber absorbing material according to claim 1, characterized in that: The viscosity of the hydroxy silicone oil is in the range of 20-40 cst, and the hydroxyl content is in the range of 7-11 mol%.
7. The foamed silicone rubber absorbing material according to claim 1, characterized in that: The peroxide crosslinking agent is selected from at least one of di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide.
8. The method for preparing the foamed silicone rubber absorbing material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Methyl vinyl silicone rubber, multi-walled carbon nanotubes, iron powder, fumed silica and hydroxy silicone oil are kneaded at 90-110° C.; after cooling to room temperature, a peroxide crosslinking agent is added and kneaded at 20-35° C. to obtain a mixture; the kneaded mixture is first vulcanized at 115-145° C. and a pressure of 9-11 MPa for 10-40 minutes to control the crosslinking degree to 40-60%; the sulfide is then injected into a supercritical fluid in a high-pressure reactor to foam under the conditions of a temperature of 60-80° C. and a pressure of 14-16 MPa, wherein the gas in the supercritical fluid is selected from at least one of carbon dioxide and nitrogen; and a foamed silicone rubber absorbing material is then secondarily vulcanized at 180-210° C. for 2-4 hours to obtain the foamed silicone rubber absorbing material.
9. The method for preparing the foamed silicone rubber absorbing material according to claim 8, characterized in that: The test method for crosslinking degree is: use dynamic mechanical analysis to test the storage modulus G' of the rubber. The storage modulus when not vulcanized is G'(0), the storage modulus when fully vulcanized is G'(∞), and the storage modulus when the vulcanization time is t is G'(t). The crosslinking degree when the vulcanization time is t is evaluated by the following formula: 。 10. The method for preparing the foamed silicone rubber absorbing material according to claim 8, characterized in that: The foaming density is controlled by adjusting the volume ratio of carbon dioxide and nitrogen in the supercritical fluid. The volume ratio of carbon dioxide and nitrogen ranges from (15-0): (0-15).